Calcitriol decreases pro-inflammatory cytokines and protects against severe hemorrhagic shock induced-organ damage in rats. (July 2016) - Tsai, Jen-Pi; Lee, Chung-Jen; Subeq, Yi-Maun; Lee, Ru-Ping; Hsu, Bang-Gee
Highlights: Hemorrhagic shock could induce hepatic, renal and pulmonary injuries and elevate the serum levels of TNF-α and IL-6. Calcitriol could alleviate HS-induced hepatic, renal and pulmonary injuries with lowering serum levels of TNF-α and IL-6. After HS, calcitriol could lessen the mortality rate independent of modulating hemodynamic status in rats. Abstract: Introduction: Resuscitation after hemorrhagic shock (HS) could result in increased pro-inflammatory cytokines and then multiple organ dysfunctions. Calcitriol exerts pleiotropic effects in a wide variety of target tissues and has a role against anti-inflammation. The present study was aimed to investigate the modulatory effects of calcitriol on the pathophysiological and inflammatory markers following HS in rats. Materials and methods: By withdrawing 60% of the total blood volume over 30 min via a femoral artery catheter in rats, HS was induced. Afterwards, 10 ng/kg calcitriol was injected intravenously in rats. After performing these procedures, hemodynamic status of mean arterial pressure (MAP) and heart rate (HR) were continuously monitored for 12 h. Hemoglobin, lactic dehydrogenase (LDH), creatine phosphokinase (CPK), liver and renal function were measured at 30 min before the induction of HS and 0, 1, 3, 6, 9, and 12 h after HS, while an equal volume of normal saline as replacement fluid. At 1 and 12 h after inducing HS, serum levels of tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) levels were measured, and the livers, kidneys and lungs were taken out and then examined histo-pathologically at 48 h after inducing HS. Results: Hemoglobin and MAP were significantly decreased, liver and renal function were significantly impaired, but HR and the levels of LDH, CPK, TNF-α and IL-6 were significantly increased after HS in rats. After being treated with calcitriol following HS resulted in better survival rate, lower serum levels of TNF-α and IL-6, and lesser hepatic, renal, and pulmonary histo-pathologic scores of injury in rats. Conclusion: Being treated with calcitriol after HS could ameliorate the pro-inflammatory reactions by modulating the effects of cytokines, which lead to prevention of subsequent major organ damages.